MANAGEMENT OF CREATIVITY - PERSPECTIVES AND DEVELOPMENT IN THE SECTOR OF CULTURE IN SERBIA (Heritage, 2025)
Culture, as a complex social phenomenon, represents the integration of material and spiritual aspects of human life, encompassing artistic expressions, ways of life, customs, moral values, language, and education. This paper explores the challenges and dynamics of managing cultural institutions in Serbia, with a focus on their adaptation to contemporary cultural and economic trends. Cultural institutions, as bearers of cultural identity and heritage, are tasked with fostering creativity and preserving cultural values while simultaneously responding to the demands of efficient and sustainable management. Given the complexity of the cultural sector, successful management of these institutions requires an interdisciplinary approach that integrates cultural, sociological, economic, political, and aesthetic dimensions. In Serbia, where cultural institutions operate within the context of post-transitional changes and shifting socio-economic conditions, their survival and development depend on their ability to address key issues such as their role in the cultural market, funding models, external positioning, and audience engagement. Although these institutions do not primarily aim for profit generation, their sustainability hinges on their capacity to balance artistic freedom with market imperatives. The paper analyzes the evolution of approaches to managing cultural institutions in Serbia, emphasizing the importance of fostering creativity and innovation as key drivers of institutional success and societal recognition. By developing new management models, cultural institutions can enhance their efficiency, strengthen their position in the cultural landscape, and ensure the continuous growth of the creative industries.
Keywords: cultural institutions, cultural policy, creativity management, cultural product, creative industries.